2012
DOI: 10.1007/978-94-007-2888-2_17
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-Associated Membranes (MAMs) as Hotspot Ca2+ Signaling Units

Abstract: The tight interplay between endoplasmic reticulum (ER) and mitochondria is a key determinant of cell function and survival through the control of intracellular calcium (Ca(2+)) signaling. The specific sites of physical association between ER and mitochondria are known as mitochondria-associated membranes (MAMs). It has recently become clear that MAMs are crucial for highly efficient transmission of Ca(2+) from the ER to mitochondria, thus controlling fundamental processes involved in energy production and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 172 publications
1
41
0
1
Order By: Relevance
“…16 Growing evidence indicates that specific proteins residing at the ER and MAMs are able to regulate mitochondrial Ca 2 þ uptake. 17,34 We pursued the hypothesis that PTEN could act as a tumor suppressor, at least in part, by modulating the transmission of Ca 2 þ from the ER to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Growing evidence indicates that specific proteins residing at the ER and MAMs are able to regulate mitochondrial Ca 2 þ uptake. 17,34 We pursued the hypothesis that PTEN could act as a tumor suppressor, at least in part, by modulating the transmission of Ca 2 þ from the ER to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous other proteins have been characterized at MAMs, underlying the importance of this subcellular domain for signaling cell fate choices. 17 Here, we provide unprecedented evidence that a fraction of cellular PTEN is localized at the ER and MAMs. We observed that during Ca 2 þ -dependent apoptosis the localization of PTEN to the ER further increase.…”
mentioning
confidence: 86%
“…Transient expression of VDAC enhanced the amplitude of agonist-dependent increases in mitochondrial matrix Ca 2+ concentration by allowing the fast diffusion of Ca 2+ from ER release sites to the inner mitochondrial membrane [118]. The specific sites of physical association between the ER and mitochondria, known as mitochondria associated membranes (MAMs), include VDAC among the proteins present at these junctions [259]. The mitochondrial chaperone glucose-regulated protein 75 (grp75) has been proposed to mediate the molecular interaction of VDAC1 with the ER Ca 2+ release channel, IP 3 R, and that a chaperone-mediated conformational coupling of the proteins enables better transfer of the Ca 2+ ions from the ER to the mitochondria [260].…”
Section: Er-mitochondria Ca 2+ Transport Vdac and Apoptosismentioning
confidence: 99%
“…, 2015). Similarly, ER–mitochondrial interaction may be important for the Pink1-Parkin pathway, which is implicated in PD (Erpapazoglou and Corti, 2015), and Ca 2+ homeostasis (Bononi et al. , 2012).…”
Section: Introductionmentioning
confidence: 99%